2021
DOI: 10.1590/1983-40632021v5167779
|View full text |Cite
|
Sign up to set email alerts
|

Weed management in the dry season: interferences in physiology and quality of Persian lime fruits

Abstract: Weed interference in young citrus orchards causes significant damages, especially when competition occurs during the dry season, when environmental resources are even more scarce. This study aimed to test the effects of interference periods and weed management on the physiology, yield and quality of Persian lime fruits, during the dry season. The experimental design was randomized blocks, with five treatments [hoeing; glyphosate application; decrease of stored water (March to May); critical water deficit (June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Examining the correlation between the physiological variables shown in Figure 1a and 1b, it becomes evident that the block with the highest transpiration rate also exhibited the highest SPAD index. This finding goes in accordance with Soares et al (2021), who reported higher SPAD index for treatments with elevated transpiration rates.…”
Section: Resultssupporting
confidence: 92%
“…Examining the correlation between the physiological variables shown in Figure 1a and 1b, it becomes evident that the block with the highest transpiration rate also exhibited the highest SPAD index. This finding goes in accordance with Soares et al (2021), who reported higher SPAD index for treatments with elevated transpiration rates.…”
Section: Resultssupporting
confidence: 92%
“…Because of its wide range of applications, the majority of the Persian lime literature focuses on findings that improve, analyze, or observe the traits, parameters and functional aspects of the fruit and its derivatives [ 27 , 28 , 29 ]. For example, research is being conducted on plant development nutrients and compounds [ 30 , 31 ], weed management [ 32 ], harvesting [ 33 ], and protection and preservation [ 34 , 35 ]. Some studies are even held in specific countries due to their unique growth features (for example Egypt [ 28 ], Mexico [ 36 ], or Brazil [ 37 ]).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alternative quality-focused approaches have similarly been proposed, such as applying genetic research to promote vegetative development and production [ 40 ], quality on certain value phases such as postharvest [ 41 ], and on vegetative growth and mineral elements’ content [ 42 ]. On the other hand, studies are centered on processes, treatments, or methods [ 43 ] with the purpose of increasing commercialization, such as cutting treatments [ 44 ], chemical management in dry seasons [ 32 ], detection of juice adulteration [ 45 ], oil extraction methods including coldpressing, solvent extraction, enzyme—assisted aqueous extraction [ 46 ], and even innovative extraction methods such a as steam distillation [ 47 ]. Furthermore, there are studies interested on how these treatments or approaches affect physical properties of the Persian Lime [ 48 , 49 ].…”
Section: Literature Reviewmentioning
confidence: 99%